Transfer of nitrogen by migratory birds in the African-Western Eurasian Flyways - Varriano Sofia (De Gruyter, 2020)
Migrating animals are known to play an important role in nutrient transfer over short distances; however, this phenomenon has not been well studied for long-distance migrants. In this preliminary study, we focused on nitrogen (N) transfer by 44 bird species that migrate from Eurasia to two regions in sub-Saharan Africa that fall into the lowest 10% quantile of global N-deposition (mean annual deposition ≤ 10.44 mg/m2/year). We estimated the number of birds that die during the non-breeding season in these areas and then used N content and species-specific mass values to calculate annual N-deposition rates. For these two areas of low N-deposition, we found that bird mortality contributed 0.2 – 1.1% of total nitrogen deposition, which is a relatively small proportion. Therefore, we conclude that nitrogen transfer by long-distance bird migrants using the East Atlantic Flyway and the West Asian-East African Flyway currently has limited impact on the sub-Saharan nitrogen cycle. However, it is worth noting that this impact may have been more important in the past due to larger bird populations and lower background N-deposition (i.e., less anthropogenic impact).